Ethics in public relations - Parsons, Patricia J. (London, 2004)
Ten years ago, I began teaching a course in organizational public relations to second-year public relations students in our four-year undergraduate degree programme. At the time, the curriculum required a section on ethics. To my colleagues in the department, I appeared to be the most likely candidate to teach this since my background was in medical communications and I had already co-authored two books one a textbook and one a trade book - on healthcare ethics. Surely this would be a natural progression for me. To some extent they were right.
Keywords: Publi relations - Moral and ethical aspects; Public relations - management